2016
DOI: 10.1136/jfprhc-2016-101541
|View full text |Cite
|
Sign up to set email alerts
|

Intended and unintended consequences of abortion law reform: perspectives of abortion experts in Victoria, Australia

Abstract: Law reform, while positive, has failed to address a number of significant issues in abortion service provision, and may have even resulted in a 'lull' in action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…However, this study2 also demonstrates that the removal of specific criminal prohibitions against abortion should not be seen as a panacea. Indeed, albeit for reasons apparently unconnected with the legal reform, it found that public service provision and access to later abortion services appear actually to have decreased in Victoria since 2008.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…However, this study2 also demonstrates that the removal of specific criminal prohibitions against abortion should not be seen as a panacea. Indeed, albeit for reasons apparently unconnected with the legal reform, it found that public service provision and access to later abortion services appear actually to have decreased in Victoria since 2008.…”
mentioning
confidence: 67%
“…Keogh et al 's2 study in this issue provides the first robust confirmation that the incidence of legal abortions has not risen since decriminalisation. Neither has the removal of criminal sanction led to more late terminations.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Timely presentation for antenatal care and financial capacity are the most likely socio‐economic influences on a women's choice of first or second trimester screening. The fact that disadvantaged women are more likely to have a prenatal diagnosis of a major trisomy after 17 weeks has important management as well as ethical implications, as surgical termination of pregnancy is less available and less affordable in Victoria after 17 weeks and entails higher surgical risks to the woman …”
Section: Discussionmentioning
confidence: 99%
“…Ideally, women should be offered prenatal screening in the first trimester, as this maximises choice and facilitates subsequent genetic counselling and prenatal diagnosis of an affected pregnancy before 17 weeks gestation. Earlier prenatal diagnosis not only is psychologically preferable for women but also improves access to surgical termination of pregnancy in Victoria if requested, as services are limited after 17 weeks gestation . Further opportunities for trisomy detection occur at the time of second trimester fetal morphology scan (typically performed at 18 to 22 weeks), but its sensitivity for T21 is lower.…”
Section: Introductionmentioning
confidence: 99%